STUDI RUMAH PANGGUNG TAHAN GEMPA WOLOAN DI MINAHASA MANADO - -, Marwati (Teknosains, 2014)
Indonesia is an archipelago with the level of risk of earthquakes is high enough, it is because the Indonesian archipelago was among four (4 ) active tectonic system. Region Minahasa is one of Indonesia is prone gempa. Arsitektur architectural wooden house on stilts, ie construction techniques that use the connection without nails or tools and materials other than wood connector.The purpose of this study was to determine the safety system of earthquake resistant buildings on the home stage of Manado wuloan aspect forms, layout, structure and construction as well as lingkungan. Kajian is done by comparing the descriptive standards and the fact the field. The results of the study stated that the Wuloan including earthquake-resistant houses stage because, of all the main frame of wooden beams Iron, each intertwined beams, the walls of the board it is not easy to crack or break and tested at the origin surrounded by volcanoes and frequent earthquakes.Key words: Main Stage, Wuloan, Earthquake Resistant.